HAMILTONIAN MODEL AND PATH INTEGRAL APPROACH ON BIOMOLECULAR DYNAMICS: DNA AND MICROTUBULES CASES. - HIDAYAT (NIM : 30212012), WAHYU
Research on the dynamics of macromolecules (molecular biology) involves an interdisciplinary science form different methods: theoretically, experimentally, and computationally. The application of theoretical physics methods in molecular biology especially in these cases: DNA and Microtubules are still interesting research to study comprehensive. In this dissertation has been investigated the energy transfer mechanism, thermodynamic behavior in the DNA and microtubules system including the effect of viscosity potential. Hamiltonian euqations has been developed to describe both of system, DNA and microtubules, hence by employing path-integral approach to calculate numerically corresponding physical quantities : the average distance of base pairs in the case of DNA denaturation, and the average length of microtubules under biologycal temperature and viscosity. The obtaining results how the effect of viscosity to compensates denaturation of DNA under increasing temperature and to supress microtubules to be easily broken or damaged. In this dissertation also show how the viscosity change the energy profile as long as propagation on DNA and microtubules. Especially in the case of DNA, the speed of DNA splitting are calculated as well as its thermodynamic properties.